2016
DOI: 10.1080/15226514.2016.1183576
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cadmium-resistant bacteria for its potential in promoting plant growth and cadmium accumulation in Sesbania bispinosa root

Abstract: The cadmium (Cd) resistant bacteria were isolated from soils of Damanganga river, Vapi, and identified 11 potential Cd resistant bacteria based on 16S rDNA sequences. The Cd resistant bacteria belonged to four different genera: Providencia spp., Morganella sp., Stenotrophomonas sp., and Bacillus spp. The assessment of plant growth-promoting (PGP) parameters revealed that the Cd tolerant bacteria showed one or more PGP properties. Further, a pot experiment was conducted to elucidate the effects of Cd resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Providencia sp. strains were tested by Kartik et al (2016) and their tolerance to elevated concentrations of Cd together with PGP effect were proven.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providencia sp. strains were tested by Kartik et al (2016) and their tolerance to elevated concentrations of Cd together with PGP effect were proven.…”
Section: Discussionmentioning
confidence: 99%
“…From among numerous strain isolates, the following ones are worth mentioning: Comamonas testosteronii, Flavobacterium sp., Methylobacterium fujisawaense, Alcaligenes piechaudii and Alcaligenes xylosooxidans ( Kanazawa and Mori, 1996 ), Klebsiella planticola ( Sharma et al, 2000 ), Cupriavidus taiwanensis and Pseudomonas aeruginosa ( Siripornaldulsil and Siripornaldulsil, 2013 ), Stenotrophomonas acidaminiphila ( Lin et al, 2016 ), Providencia spp. ( Kartik et al, 2016 ), Bacillus cereus, Alcaligenes faecalis ( El-Meihy et al, 2019 ), Rhizobium pusense ( Li et al, 2019 ), Enterobacter kobei , and Bacillus cereus ( Abdollahi et al, 2020 ), Stenotrophomonas rhizophila, Variovorax boroniumulans , and Sporosarcina pasterurii ( Jalilvand et al, 2020 ). In the context of the above it is emphasized that the bacterial species isolated in the present study have never before been obtained from saline-rich and/or Cd-containing root zones of Mesembryanthemum crystallinum and to the best of our knowledge this is the first contribution to prove the occurrence of rhizospheric salt- and Cd tolerant strains of Rhodococcus erythropolis , Paenibacillus glucanolyticus , and Providencia rettgeri .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another finding Providencia sp., Morganella sp., Stenotrophomonas sp., and Bacillus sp. were studied for their effect on plant growth and uptake of cadmium by roots of Sesbania bispinosa 37 . The bacterial strain Klebsiella pneumoniae MCC 3091 was studied for promoting the growth of rice seedling growth by lessening the phytotoxicity of cadmium 38 .…”
Section: Effect Of Bioformulations On the Growth Of Seedlingsmentioning
confidence: 99%
“…They also showed great tolerance in combination with plant growth, development and enhancement of biomass on roots and shoots Brassica juncea and B. napus[25][26][27]. Kartik et al[28] also reported bacterial strains such as Stenotrophomonas sp., Providencia spp., Bacillus spp., and Morganella sp. which showed better plant growth promoting activities and greater Cd resistance and detoxification potential in phytoremediation.…”
mentioning
confidence: 99%